LINC00968 functions as an oncogene in osteosarcoma by activating the PI3K/AKT/mTOR signaling. Issue 11 (15th June 2018) - Liu, Gang; Yuan, Dongtang; Sun, Peng; Liu, Weidong; Wu, Peng‐Fei; Liu, Huan; Yu, Guang‐Yang
Abstract : Osteosarcoma is recognized as a malignant tumor in the skeletal system. Long non‐coding RNAs (lncRNAs) have been exhibited to play crucial roles in osteosarcoma development. Our current study focused on the biological effects and mechanism of LINC00968 in osteosarcoma pathogenesis. We observed that LINC00968 was dramatically elevated in osteosarcoma cells including U2OS, MG63, Saos‐2, SW1353, and 143‐B cells compared to human osteoblast cell line hFOB. Silence of LINC00968 inhibited osteosarcoma cell growth and proliferation in vitro. Reversely, overexpression of LINC00968 promoted osteosarcoma cell survival and cell colony formation ability in Saos‐2 and 143‐B cells. In addition, LINC00968 was able to induce osteosarcoma cell migration and invasion through up‐regulating MMP‐2 and MMP‐9 protein levels. The phosphoinosmde‐3‐kinase/Protein Kinase B/mammalian target of rapamycin (PI3K/AKT/mTOR) pathway has been reported to participate in several cancer types. Here, in our study, we found that PI3K/AKT/mTOR pathway was involved in osteosarcoma progression. Knockdown of LINC00968 inactivated PI3K/AKT/mTOR signaling pathway in vitro. Subsequently, in vivo tumor xenografts were established using 143‐B cells to investigate whether LINC00968 can induce osteosarcoma development in vivo. Consistently, it was indicated that inhibition of LINC00968 significantly inhibited osteosarcoma progression in vivo. Taken these together, in our research, LINC00968 could be provided as a novel prognostic biomarker and therapeutic target in osteosarcoma diagnosis and treatment. Abstract : It was exhibited that LINC00968 inhibition can suppress osteosarcoma development by inactivating PI3K/AKT/mTOR both in vitro and in vivo. In addition, LINC00968 overexpression significantly induced osteosarcoma cell growth, proliferation, migration, and invasion. Taken these together, we concluded that LINC00968 can function as an oncogene in osteosarcoma progression by activating the PI3K/AKT/mTOR signaling pathway.